Physical dimensions of children's touchscreen interactions: Lessons from five years of study on the MTAGIC project. Issue 128 (August 2019) - Anthony, Lisa
Highlights: Five years of study examining children's touchscreen interactions compared to adults'. Data has been collected from over 180 people (60 adults, 120 children). Results focus on findings that are robust to screen size and touchscreen platform. The set of cumulative design recommendations captures in one place an easy reference for future design. Open questions in the design of touch-based interactions for children on future platforms. Abstract: Touchscreen interaction is nearly ubiquitous in today's computing environments. Children have always been a special population of users for new interaction technology: significantly different from adults in their needs, expectations, and abilities, but rarely tailored to in new contexts and on new platforms. Studies of children's touchscreen interaction have been conducted that focus on individual variables that may affect the interaction, but as yet no synthesis of studies replicating similar methodologies in different contexts has been presented. This paper reports the results across five years of focused study in one project aiming to characterize the differences between children's and adults' physical touchscreen interaction behaviors. Six studies were conducted with over 180 people (116 children) to understand how children touch targets and make onscreen gestures. A set of design recommendations that summarizes the findings across the six studies is presented for reference. This paper makes the entire set available for reference in one place and highlights where the findings are generalizable across platforms. These recommendations can inform the design of future touchscreen interfaces for children based on their physical capabilities. Also, this paper outlines the future challenges and open questions that remain for understanding child-computer interaction on touchscreens.